Injury in elite women soccer and national women soccer in the lower extremity - Blasco, E.; Paredes, A.; Monleon, C.; Martin, M.; Fargueta, M.; Elvira, L. (Journal of Human Sport & Exercise, 2018)
Purpose: Analyse the epidemiology of women's soccer harmful depending on the category of game. Materials and Methods: There were 26 participants (38 Super League and 32 National League women) with a mean age of 21.20 ± 4.64 years and body mass index (BMI) of 21.94 ± 1.79 kg/m2. There are several reasons why the health problems of the women`s soccer must be taken into account. Among these reasons, we think that the speed actions in this sport will have a great impact on the health of competitors. In addition, the women are more prone to overuse injuries due to the morphological characteristics. Results: Musculoskeletal injuries and pain were importance to women`s soccer of two levels. This was reflected in our study, the high percentage of activation muscle shortening, especially at hip external right and left rotators (100%), also at internal hip right and left rotators (100%) in the premier league. However, in national league the high percentage was at hip external right and left rotators (78.1%) and shortening in internal hip right and left rotators (90.6%). Conclusions: It is important to continue hearing the ergogenesis of this sport and particularly of women's soccer, to reduce its lesional index.